ҚАРАҚАЛПАҚ ФОЛЬКЛОРТАНЫЎ ИЛИМИНИҢ ПАЙДА БОЛЫЎЫ ҲӘМ РАЎАЖЛАНЫЎ БАСҚЫШЛАРЫ - Даўтова, Г. (SCIENCE and SOCIETY, 2023)
In the article, the stages of emergence and development of Karakalpak folkloristic science are scientifically and theoretically studied. Also, the scientific works of foreign and local scientists who researched Karakalpak folklore were recognized.